Media społecznościowe w pracy dziennikarzy w Polsce, Rosji i Szwecji : analiza porównawcza - Baranowski, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Journalists, from the point of view of political communication, are a vital occupational group. As mentioned by Perloff (1998), they are the key element in the “golden triangle,” which is the visualization of the structure of information flow between politicians and society. Technological revolution started by the internet and networked solutions has brought social network services, which quickly became the new communication tools. Nowadays, Facebook or Twitter are simultaneously used as synonyms of social media. Almost every branch of industry has found appropriate use for these tools. Since social media changed the way that society communicates and are one ofthe biggest publicly available databases of personal data, their utility was also noticed by journalists. The objective of this book is to analyze the ways of the social media use by journalists in Poland, Russia and Sweden. Three research hypotheses were assumed. The hypotheses were related to the diff erences of usage of the social media by media employees regarding the socio-demographic differences and the domination of Facebook and Twitter in the journalists’ working routine. Therefore, analysis in this book is strictly empirical and it is based on the results of surveys and in-depth interviews conducted in three analyzed countries. The data was gathered from the international research project “Journalism in change — professional journalistic cultures in Russia, Poland and Sweden.” The author of the thesis was one of the participants of the project and co-worked within the social media research group.The book consists of three parts and six chapters. The fi rst part aims to supply the reader with definitions and theoretical background of social media and journalism regarding the context of the three analyzed countries. The author also describes contemporary theories of journalism in the age of new media. The second part is focused on presenting the traditions in journalism studies empirical research in Poland, Russia and Sweden. It also highlights the role of international research initiatives in expanding the knowledge about journalists. This part also includes the methodology of the “Journalism in change” project, research questions and assumed hypotheses. The last part takes up the issue of social media in professional use of Polish, Russian and Swedish journalists. Based on gathered empirical data, the author conducts the analysis, focusing on frequency of social media use and its purpose. The book ends with an additional analysis of the journalists’ attitude towards the increased interactivity and their views on the future of the journalistic profession regarding technological progress. The conducted research has allowed the author to verify assumed research hypotheses and state that social media, apart from being professionally used by journalists, has not supplanted the traditional work tools. They turned out to be only supplementary. The data also showed that Russian journalists have used the social media most frequently, which allowed the author to falsify the first hypothesis. Regarding the second hypothesis, the age of the respondents had a visible impacton their performance while using new technologies in daily work routine. Analyzing the leading social network services, Facebook turned out to be leading platform for professional use. Only a small fraction of the research population indicated the use of Twitter, so the third hypothesis was not completely confirmed. The research on social media in journalists’ work has allowed the author to highlight the similarities and differences in the professional use of these tools among Polish, Russian and Swedish respondents. However, one should note that the analysis has covered only the declarations of journalists in surveys and in-depth interviews. The updated research with the expanded methodological workshop is undoubtedly a challenge for the future analysis of social media in the journalistic profession.
Keywords: dziennikarze -- praca -- Polska -- 1990-; dziennikarze -- praca -- Rosja -- 1990-; dziennikarze -- praca -- Szwecja -- 1990-; media społecznościowe